Socioeconomic Profile and Management Practices Followed by the Farmers Rearing Desi Birds in the Cauvery Delta Region of Tamilnadu - K. Shibi Thomas; C. Mehala (The Indian Veterinary Journal, 2023)
A study was conducted on the profile of farmers rearing desi birds in and around Orathanadu taluk of Thanjavur District. Profile of the farmer along with their practices and knowledge level was assessed using a questionnaire. The results revealed that majority of the farmers were male, middle aged, educated up to school or college, majority had poultry as primary occupation, purchased chicks mainly for family and income generation. Desi bird farms are mainly located in villages under semi-intensive system, shed as night shelter with asbestos roofing.  Farmers had more preference towards Aseel for egg and meat purpose with retail system of marketing and integrated farming system with poultry as one of the component.